PENERAPAN E-FLIPBOOK BERBANTUAN MEDIA WORDWALL UNTUK MENINGKATKAN KEMAMPUAN HASIL BELAJAR MENULIS TEKS NARASI SISWA KELAS IV SEKOLAH DASAR - Aisyah Wardatun Nisa; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to analyze the use of e-flipbooks assisted by wordwall media in improving narrative text writing skills in grade 4 elementary school students. This study uses mixed methods, which combines quantitative and qualitative analysis. The research subjects were 4th grade elementary school students. Quantitative data was collected through pretest and posttest narrative text writing tests, while qualitative data was obtained through learning observations through interviews with teachers and students. The results of the qualitative analysis show that using e-flipbooks assisted by wordwall media increases students' motivation to write, increases interactive learning, and helps them understand the structure of narrative text. Research also shows that using e-flipbooks assisted by wordwall media helps students in their learning outcomes in writing narrative texts. This can be proven by the results of increasing students' ability to develop story ideas through experiences during school holidays, the use of vocabulary and sentence structure in writing. The results of this research contribute to the development of an approach used to teach students to write narrative texts using digital media in grade 4 elementary school student.